2011
DOI: 10.1186/1297-9716-42-93
|View full text |Cite
|
Sign up to set email alerts
|

A review of Brucella infection in marine mammals, with special emphasis on Brucella pinnipedialis in the hooded seal (Cystophora cristata)

Abstract: Brucella spp. were isolated from marine mammals for the first time in 1994. Two novel species were later included in the genus; Brucella ceti and Brucella pinnipedialis, with cetaceans and seals as their preferred hosts, respectively. Brucella spp. have since been isolated from a variety of marine mammals. Pathological changes, including lesions of the reproductive organs and associated abortions, have only been registered in cetaceans. The zoonotic potential differs among the marine mammal Brucella strains. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
138
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(148 citation statements)
references
References 124 publications
(209 reference statements)
4
138
0
6
Order By: Relevance
“…These results further support the hypothesis that they may be infected by a strain of the bacteria that appears to be having little effect on their health. Other pinniped species have also been shown to be seropositive and yet remain apparently healthy and asymptomatic (Nielsen et al 1996, Retamal et al 2000, Nymo et al 2011. Together, these results indicate that the bacteria may only cause a mild and transient infection, and B. pinnipedialis is most likely not a major cause of the harbour seal decline in Scotland.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…These results further support the hypothesis that they may be infected by a strain of the bacteria that appears to be having little effect on their health. Other pinniped species have also been shown to be seropositive and yet remain apparently healthy and asymptomatic (Nielsen et al 1996, Retamal et al 2000, Nymo et al 2011. Together, these results indicate that the bacteria may only cause a mild and transient infection, and B. pinnipedialis is most likely not a major cause of the harbour seal decline in Scotland.…”
Section: Discussionmentioning
confidence: 56%
“…B. ceti infections in cetaceans have been associated with various patho logies which include abortions and neonatal mortality (Miller et al 1999), epididymitis in males (Da gleish et al 2008), meningoencephalitis (González et al 2002, Jauniaux et al 2010, Alba et al 2013, Garofolo et al 2014, abscesses , endocarditis (González-Barrientos et al 2010), mastitis, pneumonia, peritonitis, osteomyelitis and spinal discospondylitis ). In contrast, pathology associated with B. pinnipedialis in seals is lacking despite several reports of its isolation , Tryland et al 2005, Nymo et al 2011, Siebert et al 2017.With respect to harbour seals specifically, Brucella has previously been isolated from wild animals (Ross et al 1994, Garner et al 1997, Prenger-Berninghoff et al 2008, and in several areas they have also been found to be seropositive , Maratea et al 2003, Gaydos et al 2005, Hueffer et al 2013. However, the extent to which harbour seals in Scotland, or the United Kingdom in general, have been exposed to this pathogen since the onset of the de clines is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Se han reconocido diez especies de Brucella basadas sobre la especificidad del hospedero preferencial, ocho de las cuales afectan a animales terrestres (B. abortus, B. melitensis, B. suis, B. ovis, B. canis, B. neotomae, B. microti y B. inopinata) y dos que afectan a mamíferos marinos (B. ceti y B. pinnipedialis). A la vez, se han clasificado como Brucellas clásicas a B. abortus, B. melitensis y B. suis; para estas bacterias se han reconocido 7, 3 y 5 biovars, respectivamente 1,3 . De las diez especies reconocidas mundialmente, seis son capaces de infectar al ser humano; según su mayor poder patogénico e invasor, se ordenan en forma descendente como B. melitensis, B. suis, B. abortus, B.canis, B. ceti y B. inopinata.…”
Section: Características Generalesunclassified
“…De las diez especies reconocidas mundialmente, seis son capaces de infectar al ser humano; según su mayor poder patogénico e invasor, se ordenan en forma descendente como B. melitensis, B. suis, B. abortus, B.canis, B. ceti y B. inopinata. Además, debido a su alta naturaleza infecciosa, y dada su facilidad en generar micro-aerosoles, B. melitensis, B. suis y B. abortus son consideradas como potenciales armas biológicas 1,[3][4][5] . Estas bacterias pueden permanecer viables durante meses en el agua, productos animales (fecas, productos abortados, lana) y materiales de trabajo, incluyendo ropa, siempre que se mantengan condiciones de humedad alta, temperatura baja y poca luz solar.…”
Section: Características Generalesunclassified
“…B. pinnipedialis has been isolated from hooded seals or from beached animals or seemingly healthy individuals captured in their natural environment [1,27,28]. Following the isolation of Brucella from porpoises and whales in Scotland and in Northern England, serological testing was also conducted on other marine mammals that could be exposed to Brucella infections along the coasts of England and Wales.…”
Section: Brucella Cetimentioning
confidence: 99%